From a Nickel to a Token : The Journey from Board of Transportation to MTA - Sparberg, Andrew J. (Book collections on Project MUSE., 2015)
"Chronicle of twenty specific events in the history of New York's mass transit systems between 1940 and 1968, including large numbers of rare photos. 1940 to 1968 was chosen because those years bracket two sea change events - the June 1940 subway unification, and the March 1968 inception of the Metropolitan Transportation Authority (MTA)"--Provided by publisher